Family- and community-related determinants of intimate partner violence among Mexican and Puerto Rican origin mothers in fragile families. (May 2017) - Paat, Yok-Fong; Hope, Trina L.; Mangadu, Thenral; Núñez-Mchiri, Guillermina Gina; Chavez -Baray, Silvia M.
Abstract: Hispanics are frequently categorized under one homogeneous group in existing intimate partner violence research, presenting a challenge for practitioners and researchers interested in assessing potentially unique public health concerns of each subgroup. Using the Fragile Families and Child Wellbeing Study, this study examined the family- and community-related determinants of intimate partner violence experienced by mothers of Mexican and Puerto Rican descent. The respondents' self-reported physical violence and power control are two key measures of IPV. Our study found statistical differences between the Mexican and Puerto Rican origin respondents' experiences with IPV. Specifically, father infidelity and parenting concordance functioned as risk and protective factors, respectively, for the Mexican origin mothers' experiences of relational violence. In the case of the Puerto Rican origin respondents, higher level of spousal support, collective efficacy, and social disorganization were linked to less violence, while increased emotional distance and higher level of baseline education were associated with more violence. Highlights: Family and community determinants play a critical role in IPV of Hispanic mothers. Family and community determinants of IPV outcomes differed between Mexican and Puerto Rican origin mothers. Our study stresses the need to adopt a culturally- and structurally sensitive model unique to each Hispanic subgroup.